Digital technologies and data-driven delay management process for construction projects - Radman, Kambiz; Jelodar, Mostafa Babaeian; Lovreglio, Ruggiero; Ghazizadeh, Eghbal; Wilkinson, Suzanne (Frontiers in Built Environment, 2022)
One of the main challenges of construction projects is managing delays; there is still a lot to overcome to reach near-zero delays (mitigation of delays) in all construction projects. Technology and different platforms are applied to support a high volume of data flow acquired from multiple resources during the construction project life cycle; how can these automated and digital progress tracking systems be considered for more effective construction delay management? The aim is to investigate the current state of real-time technologies and their applications and assess how specific attributes of these disruptive technologies can significantly alter delay management in construction industries. Therefore, this study presents a new process-based framework for using technologies with a data lifecycle viewpoint. This research uses a four-step systematic literature review involving identification, screening, extortion-eligibility check, and selection-inclusion. Furthermore, it is followed up by a thematic content analysis on using new technologies to mitigate delays in construction projects. Key trends, themes, areas of concern for research, and limitations identified in previous literature as research gaps and future needs were documented and structured. This work presents a novel process of comprehensive classification of real-time technologies that are being used in the construction industry to acquire data, screen/analyses data, and present information through an Industry 4.0 application: IoT technologies such as sensors, RFID etc., smartphones, planning/scheduling tools (Ms Project, Primavera), and Building Information Modelling (BIM). The developed process-based framework is served as a roadmap to 1) centralise real-time communication between technologies to collect, analysis and presentation data in construction phase, 2) prepare timely reports for project managers to take proper action against those problems delaying project.